CHARACTERIZATION OF NATURAL IRON SAND FROM KATA BEACH, WEST SUMATRA WITH HIGH ENERGY MILLING (HEM) - Martha Rianna; Timbangen Sembiring; Marhaposan Situmorang; Candra Kurniawan; Eko Arief Setiadi; Anggito P Tetuko; Silviana Simbolon; Masno Ginting; Perdamean Sebayang (Jurnal Natural, 2018)
Iron sand is one of the natural resources in West Sumatra that has not been optimally utilized. One of the potential locations to get this iron sand deposits is the coast of Kata. This study aims to analyze the content and size of the iron grains found on the coast of Kata Padang Beach, West Sumatera Province. Coastal sand samples are extracted using permanent magnets to separate magnetic and non-magnetic materials. Characterization of iron sand using Scanning Electron Microscopy with Energy Dispersive X-ray (SEM-EDX) and Vibrating Sample Magnetometer (VSM). The result of characterization using SEM-EDX shows that iron sand samples contain Fe and O elements derived from Phase Magnetite (Fe3O4).  Keywords: iron sand, magnetic materials, SEM-EDX, VSM